THE INFLUENCE OF ADDITION OF GINGER FLOWER (Etlingera Elatior) FLOUR AS A NATURAL PRESERVATIVE ON CATFISH (Pangasius Hypophthalmus) NUGGET IN COLD TEMPERATURE STORAGE (± 5oC) - Tri Atika Sari; Dewita Dewita; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstrak This research was aimed to determine the effect of the addition of ginger flower (Etlingera elatior) flour as a natural preservative on catfish (Pangasius Hypophthalmus) nugget in cold temperature storage (± 5oC). The research method used was an experimental method in making catfish nugget with addition of ginger flower flour with different concentration treatments, that was N0 (without ginger flower flour), N1 (5 g of ginger flower flour), N2 (10 g of ginger flower flour), and N3 (15 g of ginger flower flour). The results showed that the treatment without addition of ginger flower flour into catfish nugget (N0) was the best treatment, with appearence 7,37%, taste 7.20%, aroma 7.92%, and texture 7.02%. Based on proximate analysis, the catfish nugget without addition of ginger flower flour had contained water, ash, protein, fat content, and Total Plate Count was 58.14%, 6.02%, 10.03%, 11.64%. Based on Total Plate Count (TPC) that N3 treatment was the best treatment with value 10.9 x 103 CFU/g. Keywords: catfish nugget, ginger flower flour, preservative